Degradable environment-friendly plastic and preparation method thereof
By adopting the synergistic action of multiple materials and optimizing the preparation process in bio-based plastics, the problem of difficult balance between performance and degradability of existing bio-based plastics is solved, and high mechanical strength and excellent biodegradability are achieved, which is suitable for a variety of high-demand application scenarios.
Patent Information
- Application Number
- CN202411798785.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
Existing bio-based plastics are difficult to balance between performance and degradability, the mechanical strength and toughness of a single component material are insufficient, the dispersion of nano-enhancers is poor, the lack of self-healing function and insufficient control accuracy of the preparation process.
The synergistic effect of a variety of materials is adopted, including polylactic acid, polyhydroxy fatty acid esters, starch-based materials, nanoenhancers, self-healing microcapsules, bio-based plasticizers and natural antioxidants. The mechanical properties and degradability of the materials are improved through optimized formulation design, surface modification treatment, self-healing microcapsules technology and precise preparation process control.
It achieves high mechanical strength, excellent biodegradability and good environmental protection characteristics, solves the problems of incomplete degradation and insufficient mechanical properties of traditional single materials, extends the service life of the materials and broadens the application scenarios.
Smart Images

Figure CN119592030A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a degradable environmentally friendly plastic and a preparation method thereof. Background Art
[0002] As environmental problems become increasingly serious, plastic pollution has become a global focus. Traditional petrochemical-based plastics are non-degradable and often form a large amount of plastic waste after widespread use, which brings a huge burden to the ecological environment. In order to cope with this problem, degradable and environmentally friendly plastics have emerged, among which bio-based plastics represented by polylactic acid (PLA) and polyhydroxyalkanoates (PHA) have been widely studied and applied.
[0003] Disadvantages of existing single-component bio-based plastics:
[0004] At present, the bio-based plastics on the market are mainly PLA and PHA. Although these materials have certain degradability and good biocompatibility, single-component materials have obvious shortcomings. PLA has high mechanical strength, but poor toughness and is prone to brittle fracture; while PHA has good toughness, but its mechanical strength and thermal stability are low. Therefore, the use of PLA or PHA alone is often difficult to meet the requirements of strength and toughness at the same time, and the degradation rate in different environments is also different, which cannot effectively cope with various practical application scenarios. This makes it difficult to achieve a balance between performance and degradability of existing environmentally friendly plastics, limiting their wide application.
[0005] Dispersion problems of reinforcing agents and insufficient interface compatibility:
[0006] In order to improve the mechanical properties of bio-based plastics, nano-enhancers are usually added to the materials. However, untreated nano-enhancers tend to agglomerate in the polymer matrix and are difficult to disperse evenly, resulting in insignificant enhancement effects. In addition, the interface bonding force between the nano-enhancer and the polymer matrix is insufficient, further limiting its enhancement of the mechanical properties of the material. The nanoparticles used in the prior art cannot fully exert their enhancement effect due to poor interface compatibility, which limits the improvement of the mechanical properties of the material and restricts the performance optimization of environmentally friendly plastics.
[0007] Lack of self-healing ability of plastic materials:
[0008] Plastic products will inevitably be subjected to various external forces during use, resulting in microcracks or microdamage. These microdamages will gradually expand over time and eventually lead to material failure. In the prior art, traditional environmentally friendly plastics lack self-repairing functions and cannot cope with such microscopic damage, resulting in a decrease in the overall performance of the material and a shortened lifespan. This shortcoming has seriously affected the promotion and application of environmentally friendly plastics, especially in some application scenarios with high requirements for mechanical properties and service life.
[0009] The control accuracy of the existing preparation process is insufficient:
[0010] In the preparation process of environmentally friendly plastics, the mixing uniformity and the control accuracy of the processing technology have an important impact on the performance of the final material. In the prior art, the traditional mixing and extrusion processes lack precise process control, resulting in unstable material structure and uneven performance, making it difficult to achieve the desired use effect. In addition, the existing process is difficult to effectively control the degradation rate of the material, making it impossible for the degradation performance of environmentally friendly plastics in different environments to meet specific needs, further limiting the diversity of its application scenarios.
[0011] Therefore, the present invention provides a degradable and environmentally friendly plastic and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention
[0012] In view of the deficiencies in the prior art, the present invention provides a degradable and environmentally friendly plastic and a method for preparing the same. The invention solves many deficiencies in the prior art by optimizing formula design, surface modification of reinforcing agents, application of self-healing microcapsule technology and precise control of the preparation process.
[0013] To achieve the above objectives, the present invention is implemented through the following technical solutions: a degradable environmentally friendly plastic, the environmentally friendly plastic comprising the following components:
[0014] Polylactic acid 20-50%;
[0015] Polyhydroxyalkanoates 10-30%;
[0016] Starch-based materials 5-20%;
[0017] Nano-enhancer 1-10%;
[0018] Self-repairing microcapsules 0.5-5%;
[0019] Bio-based plasticizer 2-10%;
[0020] Natural antioxidant 0.1-3%.
[0021] Preferably, the nano-enhancer is nano-cellulose, nano-titanium dioxide or nano-graphene that has been surface-modified, and the surface modification includes chemically modifying the surface of the nanoparticles by a silane coupling agent, an epoxy group or a carboxyl group to improve the interfacial bonding force between the nano-enhancer and the polymer matrix.
[0022] Preferably, the self-healing microcapsules contain photosensitive materials or thermosensitive materials, the photosensitive materials are organic compounds containing ultraviolet photosensitivity functional groups, including azobenzene derivatives, photosensitive benzophenone or photosensitive indoline; the thermosensitive material is microcrystalline wax that undergoes phase change at 60-80°C, and the microcapsule shell is made of polylactic acid or polycaprolactone degradable polymer materials. The microcapsules rupture or dissolve when exposed to ultraviolet light or when the temperature rises, releasing the repair agent containing epoxy resin or polyurethane inside to repair microcracks or other damage in the material.
[0023] Preferably, the plasticizer is citrate, epoxidized soybean oil or glycerol.
[0024] Preferably, the natural antioxidant is tocopherol or rosemary extract.
[0025] Preferably, a method for preparing a degradable environmentally friendly plastic comprises the following steps:
[0026] S1. Premixing polylactic acid, polyhydroxyalkanoate, starch-based material, bio-based plasticizer and natural antioxidant in proportion at 120-150° C. to obtain a uniform premix;
[0027] S2. Adding the nano-enhancer and the self-healing microcapsules to the premix at 60-80° C., mixing them by a twin-screw mixer under high shear force, introducing nitrogen during the mixing process to prevent oxidative degradation, and aging the resulting mixture at 80-100° C.;
[0028] S3, extruding the matured mixture through reaction, controlling the extrusion temperature at 160-200° C., the screw speed at 50-150 rpm, and performing injection molding or blow molding through a mold to obtain a molten material;
[0029] S4, first cooling the formed molten material through a water tank at 50-70°C, and then further cooling it to room temperature through air flow to control the crystal structure of the material;
[0030] S5. The cooled environmentally friendly plastic product is trimmed and subjected to supercritical CO2 foaming treatment to obtain a final environmentally friendly plastic product.
[0031] Preferably, nitrogen is introduced into the twin-screw mixer in step S2 during the mixing process, and the addition rate of the nano-enhancer during the mixing process is 0.1-0.5 kg / min, so that the nano-enhancer is evenly distributed in the matrix.
[0032] Preferably, the reactive extrusion in step S3 is performed by introducing a hydroxylase catalyst, wherein the content of the enzyme catalyst is 0.05-0.5% of the total weight of the polymer, so as to promote the dynamic covalent cross-linking reaction between polymer chains during the extrusion process to form a reversible cross-linking network.
[0033] Preferably, a two-stage cooling process is adopted in the cooling process of step S4, the temperature of the water cooling section is 50-70°C, and the flow rate of the air cooling section is 10-20m / s, so as to ensure that the crystal structure of the material is stably formed during the cooling process.
[0034] The present invention provides a degradable environmentally friendly plastic and a preparation method thereof, which has the following beneficial effects:
[0035] 1. The present invention adopts a composite formula including polylactic acid (PLA), polyhydroxyalkanoate (PHA), starch-based materials, nano-enhancers, self-repairing microcapsules, bio-based plasticizers and natural antioxidants, achieving the technical effects of high mechanical strength, excellent biodegradability and good environmental protection characteristics. Compared with the environmentally friendly plastic solutions that only use PLA or PHA as a single component in the prior art, the present invention not only improves the overall performance of the material through the synergistic effect of multiple materials, but also optimizes its degradation rate and process, so that the plastic material can maintain high strength and toughness, and can be efficiently degraded in the natural environment, thereby effectively solving the problems of incomplete degradation and insufficient mechanical properties of traditional single materials.
[0036] 2. The present invention improves the dispersibility and interfacial bonding of nanomaterials in polymer matrices by using surface-modified nano-enhancers, such as nanocellulose, nano-titanium dioxide or nano-graphene modified with silane coupling agents, epoxy groups or carboxyl groups, and significantly enhances the mechanical properties of environmentally friendly plastics. Compared with the technical solutions in the prior art where unmodified nanoparticles are easy to agglomerate and unevenly dispersed, resulting in insignificant enhancement effects, the modification treatment of the present invention effectively solves the problems of poor dispersibility of nanoparticles in the matrix and limited improvement of mechanical properties, thereby greatly improving the strength, toughness and durability of the material.
[0037] 3. The present invention introduces self-healing microcapsule technology. The microcapsule contains photosensitive or thermosensitive materials, which can trigger the microcapsule to rupture or dissolve under specific ultraviolet light irradiation or temperature rise conditions, release the internal repair agent, and automatically repair the microcracks or damage in the material, thereby extending the service life of the material. Compared with the technical solutions in the prior art that plastic materials cannot self-heal after suffering micro-damage, resulting in overall performance degradation or even early failure, the present invention significantly improves the durability and reliability of the material, and is particularly suitable for application scenarios with high requirements for mechanical properties and service life, effectively solving the problem of easy damage and short life of traditional environmentally friendly plastics in long-term use.
[0038] 4. The preparation method of the present invention innovatively combines the high shear mixing technology of a twin-screw mixer, the uniform dispersion process under nitrogen protection, and the enzyme-catalyzed dynamic covalent bond cross-linking technology, ensuring the uniformity of the material, enhancing its mechanical properties, and achieving the controllability of the degradation performance. Compared with the technical solutions in the prior art that lead to unstable material performance and difficult to control degradation rate due to imprecise process control, the present invention solves the problems of uneven mixing, unstable structure, and difficult to control degradation in the traditional preparation process through a precise process flow, significantly improving the quality and performance of the final product, and broadening its application potential in high-demand environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The present invention is a flow chart of the preparation method of degradable and environmentally friendly plastics. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example:
[0042] Please see attached Figure 1 :
[0043] Embodiment 1:
[0044] Material ratio:
[0045] Polylactic acid (PLA): 35%
[0046] Polyhydroxyalkanoate (PHA): 25%
[0047] Starch-based materials: 15%
[0048] Nanocellulose (treated with silane coupling agent): 5%
[0049] Self-healing microcapsules (photosensitive materials): 3%
[0050] Bio-based plasticizer (epoxidized soybean oil): 10%
[0051] Natural antioxidant (tocopherol): 2%
[0052] Preparation steps:
[0053] At 130° C., polylactic acid, polyhydroxyalkanoate, starch-based material, bio-based plasticizer and natural antioxidant were put into a twin-screw mixer in proportion and premixed for 30 minutes to obtain a uniform premix.
[0054] At 70°C, nanocellulose modified with silane coupling agent and self-healing microcapsules were added to the premix and mixed under high shear force for 20 minutes using a twin-screw mixer. Nitrogen was introduced to prevent oxidative degradation of the material. The mixture was matured at 90°C for 1 hour to ensure the uniformity and stability of the mixture.
[0055] The matured mixture is extruded through a reaction extruder, the extrusion temperature is controlled at 180° C., the screw speed is 100 rpm, and injection molding is performed through a mold to obtain a uniform molten material.
[0056] The molten material is cooled in a 60°C water tank and further cooled to room temperature by air flow in order to control the crystal structure of the material and ensure the stability and mechanical properties of the finished product.
[0057] The cooled environmentally friendly plastic products are trimmed and finally subjected to supercritical CO2 foaming treatment to obtain environmentally friendly plastic products with excellent strength and toughness.
[0058] Summary of Examples: Example 1 not only enhances the mechanical properties of the material by adding starch-based materials and modified nanocellulose to PLA and PHA, but also gives the material the ability to self-heal by adding photosensitive self-repairing microcapsules. This combination enables the material to automatically repair microcracks under light conditions and extend its service life while meeting the requirements of high strength and toughness.
[0059] Embodiment 2:
[0060] Material ratio:
[0061] Polylactic acid (PLA): 30%
[0062] Polyhydroxyalkanoate (PHA): 20%
[0063] Starch-based materials: 10%
[0064] Nano titanium dioxide (after epoxy group treatment): 7%
[0065] Self-healing microcapsules (thermosensitive materials): 4%
[0066] Bio-based plasticizer (citrate ester): 8%
[0067] Natural antioxidant (rosemary extract): 1%
[0068] Preparation steps:
[0069] At 140°C, polylactic acid, polyhydroxyalkanoate, starch-based material, bio-based plasticizer and natural antioxidant were put into a mixer in proportion and premixed for 40 minutes to ensure that all components were fully integrated to obtain a uniform premix.
[0070] At 75°C, nano-titanium dioxide modified with epoxy groups and thermosensitive self-healing microcapsules were added to the premix and mixed under high shear force for 25 minutes using a twin-screw mixer. Nitrogen was introduced during the mixing process to prevent oxidative degradation of the material. The resulting mixture was aged at 85°C for 1.5 hours to ensure uniform distribution of the reinforcing agent and stability of the microcapsules.
[0071] The matured mixture was blow-molded by a reaction extruder, the extrusion temperature was controlled at 170° C., the screw speed was 120 rpm, and a uniform molten material was formed.
[0072] The formed molten material is cooled in a 55°C water tank and further cooled to room temperature by air flow in order to control the crystal structure of the material and ensure the strength and toughness of the product.
[0073] The cooled environmentally friendly plastic products are trimmed and finally subjected to supercritical CO2 foaming treatment to obtain environmentally friendly plastic products with good self-repairing ability.
[0074] Summary of Examples: Example 2 adds modified nano titanium dioxide and thermosensitive self-healing microcapsules to PLA and PHA, further enhancing the mechanical properties and self-healing ability of the material. Different from Example 1, this example uses thermosensitive microcapsules, which enable the material to automatically repair microcracks under heating conditions, and is suitable for temperature-sensitive application scenarios, such as food packaging.
[0075] Embodiment 3:
[0076] Material ratio:
[0077] Polylactic acid (PLA): 40%
[0078] Polyhydroxyalkanoate (PHA): 15%
[0079] Starch-based materials: 10%
[0080] Nanographene (treated with carboxyl groups): 5%
[0081] Self-healing microcapsules (photosensitive materials): 2%
[0082] Bio-based plasticizer (glycerol): 8%
[0083] Natural antioxidant (tocopherol): 1%
[0084] Preparation steps:
[0085] At 135°C, polylactic acid, polyhydroxyalkanoate, starch-based material, bio-based plasticizer and natural antioxidant were put into a mixer in proportion and pre-mixed for 35 minutes to ensure uniform mixing of the components.
[0086] At 65°C, nanographene modified with carboxyl groups and photosensitive self-healing microcapsules were added to the premix and mixed under high shear force for 30 minutes using a twin-screw mixer. Nitrogen was introduced during the mixing process to prevent oxidative degradation of the material. The mixture was aged at 95°C for 2 hours to ensure the uniformity and stability of the material.
[0087] The matured mixture was injection molded by a reaction extruder, the extrusion temperature was controlled at 185° C., the screw speed was 110 rpm, and a uniform molten material was formed.
[0088] The formed molten material is cooled in a 65°C water tank and further cooled to room temperature by air flow in order to control the crystal structure of the material and ensure that the finished product has excellent mechanical properties.
[0089] The cooled environmentally friendly plastic products are trimmed and finally subjected to supercritical CO2 foaming treatment to obtain environmentally friendly plastic products with higher strength.
[0090] Summary of Examples: Example 3 significantly improves the strength and self-healing performance of the material by adding modified nanographene to PLA and PHA and combining it with photosensitive self-healing microcapsules. Compared with Examples 1 and 2, the mechanical strength of the material is further improved by using nanographene as a reinforcing agent. At the same time, the photosensitive self-healing function ensures the self-healing performance of the material under light conditions, which is suitable for application in outdoor environments.
[0091] Result analysis between embodiments:
[0092] Example 1 and Example 3 used photosensitive microcapsules, but Example 3 showed higher mechanical strength due to the difference in nano-reinforcement agents. This is because the reinforcing effect of nanographene is better than that of nanocellulose, even though both are modified. The photosensitive microcapsules performed the same in both materials and were able to repair microcracks under ultraviolet light.
[0093] The thermosensitive microcapsules of Example 2 exhibit good self-healing ability when the temperature rises, and are suitable for scenarios requiring temperature control. However, compared with the photosensitive microcapsules, the thermosensitive microcapsules contribute less to the overall strength of the material.
[0094] Comparative experiment:
[0095] Comparative experiment 1: strength and toughness comparison
[0096] Experimental process:
[0097] Preparation of contrast materials:
[0098] Formulation 1 (Comparative Material A): 100% PLA, no other components.
[0099] Formulation 2 (Comparative Material B): 100% PHA, no other components.
[0100] Formulation 3 (materials of Example 1 of the present invention).
[0101] Formula 4 (materials of Example 2 of the present invention).
[0102] Formula 5 (materials of Example 3 of the present invention).
[0103] Test indicators:
[0104] Tensile strength was measured using standard tensile testing equipment.
[0105] The elongation at break was measured using an elongation at break measuring instrument.
[0106] The impact strength was measured using an impact tester.
[0107] Experimental results table:
[0108]
[0109] Analysis summary:
[0110] The strength of Example 3 is the highest, which is attributed to the reinforcing effect of nanographene. Examples 1 and 2 have better toughness and are suitable for applications requiring material flexibility.
[0111] Although the comparative materials A (pure PLA) and B (pure PHA) have high strength or high toughness respectively, they cannot meet the requirements of both strength and toughness at the same time, while the material of the present invention achieves a good balance in terms of strength and toughness.
[0112] Comparative experiment 2: Comparison of nano-enhancement agent dispersion
[0113] Experimental process:
[0114] Preparation of contrast materials:
[0115] Formulation 1 (Comparative Material A): Unmodified nanocellulose reinforced plastic.
[0116] Formulation 2 (comparative material B): plastic reinforced with nanocellulose modified with a silane coupling agent (Example 1).
[0117] Test method:
[0118] Transmission electron microscopy (TEM) was used to observe the dispersion of the nanoreinforcement agents in the matrix.
[0119] Experimental results:
[0120] Formulation 1 showed severe agglomeration and uneven distribution of nanocellulose.
[0121] Formulation 2 (Example 1) showed that the nanocellulose was evenly dispersed in the matrix without obvious agglomeration.
[0122] Analysis summary:
[0123] Surface modification significantly improved the dispersibility of nanocellulose in the matrix and enhanced the mechanical properties of the material.
[0124] Comparative experiment 3: Comparison of self-repair capabilities
[0125] Experimental process:
[0126] Preparation of contrast materials:
[0127] Formulation 1 (Comparative Material A): PLA / PHA-based plastic without self-healing microcapsules.
[0128] Formulation 2 (comparative material B): plastic of the present invention containing photosensitive self-healing microcapsules (Example 1).
[0129] Formulation 3 (Comparative Material C): Plastic of the present invention containing thermosensitive self-healing microcapsules (Example 2).
[0130] Test method:
[0131] The samples were stretched until microcracks were generated, and then exposed to UV light or elevated temperature for 1 hour, and the repair of the cracks was observed.
[0132] Experimental results table:
[0133] Material Type Repair rate (%) Plastic without self-healing function (A) 0 Photosensitive self-healing microcapsule plastic (B) 85 Thermosensitive self-healing microcapsule plastic (C) 80
[0134] Analysis summary:
[0135] Materials containing photosensitive and thermosensitive microcapsules exhibit excellent self-healing capabilities, which greatly extend the service life of the materials compared to plastics without self-healing functions.
[0136] The repair efficiency of photosensitive microcapsules was slightly higher than that of thermosensitive microcapsules, which may be because the photosensitive repair agent was released faster under UV light irradiation.
[0137] Comparative experiment 4: Preparation process comparison
[0138] Experimental process:
[0139] Preparation of comparison process:
[0140] Comparative process A: conventional twin-screw compounding process without nitrogen introduction.
[0141] Comparative process B: The process of the present invention adopts a high shear mixing process under nitrogen protection.
[0142] Test method:
[0143] The distribution of nanoreinforcements in the material was observed by transmission electron microscopy (TEM).
[0144] Test the uniformity and strength of materials.
[0145] Experimental results:
[0146] In the material of comparison process A, the distribution of the reinforcing agent is uneven, and there is obvious aggregation in some areas.
[0147] In the material of the comparative process B, the reinforcing agent is evenly distributed without obvious aggregation.
[0148] Analysis summary:
[0149] The process of the present invention can significantly improve the dispersion uniformity of the nano-enhancer, ensure the uniformity and mechanical properties of the final material, and avoid the performance fluctuation problem existing in the conventional process.
[0150] Summarize:
[0151] Through the analysis of the above examples and comparative experiments, the degradable and environmentally friendly plastic of the present invention has shown significantly better performance than the prior art in terms of strength and toughness, reinforcing agent dispersion, self-repairing ability, and uniformity of the preparation process. These improvements significantly improve the practicality and application range of the material, making the present invention have obvious technical advantages in a variety of high-demand applications.
[0152] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A degradable environmentally friendly plastic, characterized in that: The environmentally friendly plastic comprises the following components: Polylactic acid 20-50%; Polyhydroxyalkanoates 10-30%; Starch-based materials 5-20%; Nano-enhancer 1-10%; Self-repairing microcapsules 0.5-5%; Bio-based plasticizer 2-10%; Natural antioxidant 0.1-3%.
2. A degradable and environmentally friendly plastic according to claim 1, characterized in that: The nano-enhancer is nano-cellulose, nano-titanium dioxide or nano-graphene that has been surface-modified, and the surface modification includes chemically modifying the surface of the nanoparticles through a silane coupling agent, an epoxy group or a carboxyl group.
3. The degradable and environmentally friendly plastic according to claim 1, characterized in that: The self-repairing microcapsule contains a photosensitive material or a thermosensitive material. The photosensitive material is an organic compound containing an ultraviolet photosensitive functional group, including an azobenzene derivative, a photosensitive benzophenone or a photosensitive indoline; the thermosensitive material is a microcrystalline wax that undergoes a phase change at 60-80°C. The microcapsule shell is made of a degradable polymer material of polylactic acid or polycaprolactone. The microcapsule breaks or dissolves when exposed to ultraviolet light or the temperature rises, releasing a repair agent containing epoxy resin or polyurethane inside.
4. The degradable and environmentally friendly plastic according to claim 1, characterized in that: The plasticizer is citrate, epoxidized soybean oil or glycerin.
5. The degradable and environmentally friendly plastic according to claim 1, characterized in that: The natural antioxidant is tocopherol or rosemary extract.
6. A method for preparing a degradable and environmentally friendly plastic according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Premixing polylactic acid, polyhydroxyalkanoate, starch-based material, bio-based plasticizer and natural antioxidant in proportion at 120-150° C. to obtain a uniform premix; S2. Adding the nano-enhancer and the self-healing microcapsules to the premix at 60-80° C., mixing them by a twin-screw mixer under high shear force, introducing nitrogen during the mixing process to prevent oxidative degradation, and aging the resulting mixture at 80-100° C.; S3, extruding the matured mixture through reaction, controlling the extrusion temperature at 160-200° C., the screw speed at 50-150 rpm, and performing injection molding or blow molding through a mold to obtain a molten material; S4, first cooling the formed molten material through a water tank at 50-70°C, and then further cooling it to room temperature through air flow to control the crystal structure of the material; S5. The cooled environmentally friendly plastic product is trimmed and subjected to supercritical CO2 foaming treatment to obtain a final environmentally friendly plastic product.
7. The method for preparing a degradable and environmentally friendly plastic according to claim 6, characterized in that: The twin-screw mixer in step S2 is fed with nitrogen during the mixing process, and the addition rate of the nano-enhancer during the mixing process is 0.1-0.5 kg / min, so that the nano-enhancer is evenly distributed in the matrix.
8. The method for preparing a degradable and environmentally friendly plastic according to claim 6, characterized in that: The reactive extrusion in step S3 is carried out by introducing a hydroxylase catalyst, wherein the content of the enzyme catalyst is 0.05-0.5% of the total weight of the polymer, so as to promote the dynamic covalent cross-linking reaction between polymer chains during the extrusion process to form a reversible cross-linking network.
9. The method for preparing a degradable and environmentally friendly plastic according to claim 6, characterized in that: The cooling process of step S4 adopts a two-stage cooling process, the temperature of the water cooling section is 50-70° C., and the flow rate of the air cooling section is 10-20 m / s.
Citation Information
Cited By
High-barrier environment-friendly packaging film with antibacterial function
CN120645531A
High-barrier environment-friendly packaging film with antibacterial function
CN120645531B
Preparation method of degradable bio-based pressure-sensitive adhesive and environment-friendly adhesive tape product
CN120818324A
Environment-friendly furniture protective film and preparation method thereof
CN120923834A